Advances in seismic imaging of mantle transition zone discontinuities - Chunquan Yu; Juan Li; Fan Yang; Yan Zhang (地球与行星物理论评, 2023)
Located between the 410-km and 660-km discontinuities, the mantle transition zone is the key region for understanding the thermal and chemical structure and the dynamic evolution of the Earth’s mantle. The top and bottom boundaries of the mantle transition zone correspond to mineral phase transitions from olivine to wadsleyite and ringwoodite to bridgmanite and ferropericlase, respectively. This paper summarizes the main seismological methods for studying and related research progress of the mantle transition zone discontinuities. These methods include SS and PP precursors, receiver functions, ScS reverberations, P'P' precursors, waveform modeling of seismic triplications, reflected body waves retrieved from ambient noise interferometry, etc. Overall, there is a positive correlation between the thickness of the mantle transition zone and velocity perturbations in the mantle transition zone on the large-scale structure, indicating that they are both mainly controlled by mantle temperature, consistent with the prediction of olivine phase transitions. However, the lack of negative correlation between 410-km and 660-km discontinuity topography, which is expected from olivine phase transitions, suggests that either the thermal structure is not coherent across the mantle transition zone vertically or there are lateral varitions in water content or mantle chemical composition. The strength (including velocity, density and impedance jumps) and width of the 410-km and 660-km discontinuities are mainly controlled by the chemical composition and water content of the mantle transition zone. Some studies also detected 520-km and 560-km discontinuities within the mantle transition zone, which might be caused by the phase transition from wadsleyite to ringwoodite and the exsolution of calcium-perovskite from majorite, respectively. The seismically detected low-velocity zones above and below the mantle transition zone may be related to the dehydration melting caused by hydrated mantle transition zone material entering the low water-solubility upper and lower mantle. Although great progresses have been made, many important scientific questions related with the mantle transition zone remain unsolved. Accurate and reliable seismic imaging of the mantle transition zone provides crucial information for understanding these questions. Multidisciplinary studies integrating seismology, mineral physics, geodynamics and geochemistry are also needed. Finally, this paper discusses some future seismological research directions of the mantle transition zone.